Chimamanda Ngozi Adichie’s Feminist Manifesto as a Compilation of Her Major Topics - Edit Fazakas (Acta Universitatis Sapientiae: Philologica)
Her award-winning novels and thought-provoking TED talks propelled the Nigerian writer Chimamanda Ngozi Adichie into the public consciousness and sparked a worldwide discourse about feminism in the late 2010s. Adichie uses her work to empower women all around the world to dismantle gender constructs, stereotypes, and sexualities designed to enslave women in society. Several researchers have successfully construed common motifs in her fiction. This paper draws on recent studies undertaken by Moffat Sebola, who affirms that Adichie’s Dear Ijeawele, or A Feminist Manifesto in Fifteen Suggestions (2017) is not only a list of proposals; with closer examination, the manifesto reveals the recurring themes throughout Adichie’s writing. Furthermore, for analytical convenience, Moffat Sebola (2022) selects only seven of Adichie’s fifteen suggestions, identifies the elements that reflect her authorial perspective, and utilizes them as filters in analysing the author’s novels. The main objective of this study has been the presentation of the elements of Adichie’s fiction in all fifteen manifesto statements. In order to achieve this objective, themes of womanhood, femininity, love, history, culture, gender equality, and otherness are discussed in separate sections with examples from her novels. The first section of the paper provides a brief overview of African feminist fiction within which the work of this third-generation Nigerian writer is embedded.